Cognitive Behavior Therapy Pada Individu Yang Mengalami Depresi - Irpan Zuhri; Faridah Ainur Rohmah (Psikostudia : Jurnal Psikologi, 2023)
Depression is an important issue in mental health that needs special attention. The subjects in this study were 23-year-old early adults with depressive disorders. This study used a quantitative experimental approach using a single case pretest posttest design. Data collection methods used by researchers are observation, interviews, and psychological tests. The psychological tests given to the subjects were cognitive tests, namely the Weschler Adult Intelligence Scale (WAIS) test, personality tests, namely the Graphic, Wartegg, and Rorschach tests as well as the Sack's Sentence Completion Test (SSCT) inventory test and the Beck Depression Inventory (BDI) test. The intervention used is Cognitive Behavior Therapy. The target of the intervention is to change the subject's cognitive distortions into more realistic thoughts so that the subject's depression can be overcome. The results of the intervention showed that Cognitive Behavior Therapy was effective in reducing the subject's depression. This is shown from the Beck Depression Inventory Test, namely the subject's level of depression is at the level of mild depression with a score of 12 and after a series of interventions it decreases to a normal level with a score of 8.Depresi merupakan salah satu isu penting dalam kesehatan mental yang perlu mendapatkan perhatian khusus. Subjek dalam penelitian ini adalah individu dewasa awal berusia 23 tahun yang mengalami gangguan depresi. Penelitian ini menggunakan pendekatan kuantitatif eksperimen dengan menggunakan rancangan single case pre test post test. Metode pengumpulan data yang dilakukan peneliti yaitu observasi, wawancara, dan tes psikologi. Tes psikologi yang diberikan kepada subjek berupa, tes kognitif yaitu tes Weschler Adult Intelligence Scale (WAIS), tes kepribadian yaitu tes Grafis, Wartegg, dan Rorschach serta tes inventori Sack’s Sentence Comletion Test (SSCT) dan tes Beck Depression Inventory (BDI). Intervensi yang digunakan adalah Cognitive Behavior Therapy. Target intervensi adalah mengubah distorsi kognitif subjek menjadi pemikiran yang lebih realistis sehingga depresi yang dialami subjek dapat teratasi.  Hasil intervensi menunjukkan bahwa Cognitive Behavior Therapy Efektif dalam menurunkan depresi yang dialami subjek. Hal ini ditunjukkan dari Tes Beck Depression Inventory yaitu tingkatan depresi subjek berada pada tingkatan depresi ringan dengan skor 12 dan setelah dilakukan serangkaian intervensi menurun berada pada tingkatan normal dengan skor 8.